Doped BaTiO3 cuboctahedral nanoparticles: Role of copper in photocatalytic degradation of dyes - P.I. Uma; U. Sandhya Shenoy; D. Krishna Bhat (Applied Surface Science Advances, 2023)
The discovery of perovskite oxides as photocatalysts has opened unique possibilities for the degradation of pollutants such as dyes. In this work, we carry out both theoretical and experimental study for the design and preparation of copper doped BaTiO3. To begin with, First principles electronic structure calculations revealed the presence of additional levels at the top of the valence band after doping copper, which considerably decreased the band gap making the oxide visible light active. Later, single pot synthesis of copper doped BaTiO3 led to production of a material which was photocatalytically active in degrading both cationic and anionic dyes. From our work, we found that the photocatalyst 0.5 CuBTO decomposed 98.2% of methylene blue dye in 120 min and 99.4% of rose bengal dye within 45 min. Such high efficiency was attributed to the high surface area, appropriate band gap and low recombination rate of the charge carriers.